Perlindungan Hukum Nasabah Perbankan Dalam Penggunaan Layanan Electronic Banking (E-Banking) (Studi di Kantor Cabang Pembantu Bank Negara Indonesia, Kertosono, Nganjuk) - Mochammad Alfin Ramdhan; M. Ilham Fajry Akbar (JOSH: Journal of Sharia, 2025)
This study discusses the legal protection of customers related to bank services in electronic banking services. The problem or problem formulation of this research is how is the legal protection of customers related to the use of electronic banking services (E-Banking) and what is the form of legal protection provided by Bank Negara Indonesia, Kertosono, Nganjuk to customers in the event of a loss in electronic banking transactions (E-Banking). This research method is empirical, namely sociological legal research and can also be called field research, and is strengthened by normative methods. Sources of legal materials used are primary, secondary and tertiary legal data sources. And using the techniques of collecting legal materials by interview and observation and literature study. The results show that the legal protection of customers using electronic banking services has not been regulated in any regulations even though the bank itself already has a banking law, but in this case the customer is a consumer, which means that the customer's rights are automatically protected by Law No.8 of 1999 concerning consumer and bank protection in providing legal protection to customers of electronic banking services if they experience a loss, refer to the Financial Services Authority Circular Lette No. 2/SEOJK.07/2014.